Engineering design an introduction - Karsnitz, John R.; O'Brien, Stephen; Hutchinson, John P. (Delmar Cengage Learning, 2013)
This book presents an overview of the basic engineering principles and concepts that shape today's modern world and includes activities and student explorations as learning tools.